2013
DOI: 10.15605/jafes.028.02.09
|View full text |Cite
|
Sign up to set email alerts
|

The Transformation of Transsexual Individuals

Abstract: The traditional binary classification of gender is repeatedly challenged throughout history with the presence of transgenders. Under the umbrella of transgenderism is transsexualism which pertains to individuals who identify with or desire to become the opposite sex. Transsexualism or Gender Dysphoria is classified as a medical condition under ICD 10 and DSM-5. The proposed treatment is sex reassignment that includes all treatments carried out to adapt to the desired sex. Sex reassignment involves a multidisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…18,32 Furthermore, in our study, patients demonstrated higher proportions of opting for breast surgery than genital or laryngeal surgeries. These findings are consistent with previous studies done locally, 33 and elsewhere, 34,35 which reported that pursuing and opting for breast surgery was consistently more prevalent than genital or laryngeal surgeries. We hypothesize several reasons that may explain our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…18,32 Furthermore, in our study, patients demonstrated higher proportions of opting for breast surgery than genital or laryngeal surgeries. These findings are consistent with previous studies done locally, 33 and elsewhere, 34,35 which reported that pursuing and opting for breast surgery was consistently more prevalent than genital or laryngeal surgeries. We hypothesize several reasons that may explain our findings.…”
Section: Discussionsupporting
confidence: 92%
“…10 In addition, costs were also determined as a barrier to genital surgery with transgender people in the country prioritizing breast surgery and laryngeal trimming, which are more affordable than genital procedures. 33 Secondly, a previous study has suggested that breast surgery may be deemed more valuable for the external presentation of one's gender identity as it is seemingly more evident compared with genitalia. 35 In a cohort study among transmasculine individuals, 94% of participants regarded breast surgery with high importance.…”
Section: Discussionmentioning
confidence: 99%
“…Having a feminine name is universal among male-to-female transsexuals. 7,8,[12][13][14] Total absence of sexual attraction and arousal towards women in this study was consistent with previous reports; universally, the transsexuals found males to be sexually appealing instead. 9,15 Identical to previous descriptions, sexual fantasies of having intercourse with a male partner were also necessary for a husband-and-wife sexual relationship, as mentioned in a previous study.…”
Section: Discussion and Recommendationsupporting
confidence: 92%
“…Second, no hormones are approved for GAHT in the Philippines. 16 Anecdotally and in other studies, trans people get their hormones from unregulated sources, such as unlicensed providers, 8 26 37 abroad, 11 16 online, 8 11 26 37 38 grey market 37 and peers. 8 11 26 33 37 Many TW use OCPs despite being not recommended not only because these are ineffective for achieving recommended serum hormonal concentrations but also because these contain ethinyl oestradiol, putting trans people at heightened risk for cardiovascular issues.…”
Section: Discussionmentioning
confidence: 99%